Low-profile, Ultra-wideband, Cavity-backed Spiral Antennas. - Rahman, Nahid. (2017)
Abstract: Spiral antennas are a popular class of antennas that demonstrate exceptionally large bandwidths, uniform input impedance, stable gains and the ability to radiate circularly polarized waves over their entire frequency coverage. Circularly polarized radiators are integral components of all space-based communication, SATNAV and SATCOM services, microwave direction finding systems, GPS applications, in-flight connectivity etc. As a result, spiral and helical elements have become a distinctive branch in the field of antenna engineering. Spiral antennas are often configured with a metallic cavity that restricts the radiation to one hemisphere for unidirectional operation. With ever-decreasing dimensions of communication devices and to focus on issues concerning space constraints arising from installation of numerous antenna elements, low-profile geometries have drawn considerable research interest over the years. In this dissertation, we have addressed the problem of designing low-profile, ultra-wideband (UWB), 2-18 GHz cavity-backed spiral antennas. First, we discuss the development of UWB shallow, absorptive cavities from a microwave material characterization standpoint. We then proceed onto geometrically modifying regular spirals to obtain more compact structures that incorporate certain radiation properties. Axial ratio is one the most important bandwidth factors in measuring the performance of a circularly polarized radiator. In developing low-profile geometries, one most often encounters the problem of deterioration of the axial ratio. This is particularly evident in rectangular spiral antennas, where the purity of the circularly polarized waves is highly compromised as a tradeoff with available aperture. It therefore becomes essential to design spiral geometry in such a way so as to preserve the lowest possible antenna aperture with the best possible axial ratio performance. In our work, we have presented a detailed study of slow wave spirals, elliptical spirals and modified Archimedean polygonal spiral antenna designs that address the problem of maintaining high axial ratio performance with low-profile planar geometries. The designed antenna systems have been fabricated and tested for performance validation, and they demonstrate excellent axial ratio characteristics across their bandwidth.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Electrical Engineering.; Advisor: Mohammed Afsar.; Committee: Joseph Noonan, Sameer Sonkusale, and Robert Mailloux.; Keywords: Electrical engineering, and Electromagnetics.